Mechanisms of Action of Novel Drugs Targeting Angiogenesis-Promoting Matrix Metalloproteinases - Fields, Gregg B. (Frontiers in Immunology, 2019)
Angiogenesis is facilitated by the proteolytic activities of members of the matrix metalloproteinase (MMP) family. More specificity, MMP-9 and MT1-MMP directly regulate angiogenesis, while several studies indicate a role for MMP-2 as well. The correlation of MMP activity to tumor angiogenesis has instigated numerous drug development programs. However, broad-based and Zn2+-chelating MMP inhibitors have fared poorly in the clinic. Selective MMP inhibition by antibodies, biologicals, and small molecules has utilized unique modes of action, such as (a) binding to protease secondary binding sites (exosites), (b) allosterically blocking the protease active site, or (c) preventing proMMP activation. Clinical trials have been undertaken with several of these inhibitors, while others are in advanced pre-clinical stages. The mechanistically non-traditional MMP inhibitors offer treatment strategies for tumor angiogenesis that avoid the off-target toxicities and lack of specificity that plagued Zn2+-chelating inhibitors.